Pine fruit as a media for planting white oyster mushroom (Pleurotus ostreatus). Issue 1 (November 2021) - Taskirawati, I; Askar, A; Baharuddin,
Abstract: Oyster mushroom is a wood fungus that can grow naturally on dead or weathered trees (saprophytes). The commonly used planting medium for oyster mushroom cultivation is sawn waste from various trees. However, considering the high rate of deforestation, ranging from illegal logging, forest burning, and conversion of forest land functions, it is necessary to make substitutions in terms of the leading media for the growth of oyster mushrooms. In this study, pine fruit is the primary medium for the growth of oyster mushrooms to add alternative materials for growing oyster mushrooms. This study aims to determine the potential of pine fruit as a growth medium for oyster mushroom ( Pleurotus ostreatus ) by the soaking method using two treatments, namely cold and hot water immersion. In cold water samples, the pine cone powder was soaked for five days, seven days, and nine days for hot water soaked for 1 hour, 2 hours, and 3 hours. The research procedure started preparing oyster mushroom growth media, inoculation, maintenance and growth, and harvesting. The results showed that oyster mushrooms could grow at media soaking in hot water for 2 hours (P2) and 3 hours (P3). Treatments P2 and P3 took 78 days and 105 days, respectively, to grow oyster mushrooms.